GENRE BASED APPROACH FOR TECAHING ESL AND EFL WRITING: SYSTEMATIC LITERATURE REVIEW - Forsia, Lastry; Muhidin, Asep (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2025)
In the last decade, the usage of genre-based approaches (GBAs) has proliferated especially in the English education sector. This article presents an analysis of a systematic review based on published studies on the genre-based approach (GBA) in teaching writing. It aims synthesize current research findings on the implementation and effectiveness of GBA, to show how GBA enhances students’ writing skill, as well as the research trends related to GBA in teaching ESL/EFL writing. Using databases such as Scopus, ERIC, Francis & Taylor, google Schoolar and etc., studies published from 2019-2025 with a total of twenty studies. This review used thematic analysis to categorize the main themes that emerge in the selected studies. The review reveals that GBA significantly enhances learners’ genre awareness, textual organization, and communicative competence through explicit instruction and scaffold learning stages. However, it also identifies major challenges, including limited teacher knowledge of genre theory, lack of institutional support, and contextual constraints in exam-oriented curricula. Overall, this review confirms that GBA is an effective and contextually adaptable framework for developing writing proficiency in ESL/EFL classrooms, while also highlighting the need for further longitudinal and technology-integrated studies to strengthen its pedagogical application.